Distinct changes to hippocampal and medial entorhinal circuits emerge across the progression of cognitive deficits in epilepsy - Yu Feng; Keziah S. Diego; Zhe Dong; Zoé Christenson Wick; Lucia Page-Harley; Veronica Page-Harley; Julia Schnipper; Sophia I. Lamsifer; Zachary T. Pennington; Lauren M. Vetere; Paul A. Philipsberg; Ivan Soler; et al. (Cell Reports)
Summary: Temporal lobe epilepsy (TLE) causes pervasive and progressive memory impairments, yet the specific circuit changes that drive these deficits remain unclear. To investigate how hippocampal-entorhinal dysfunction contributes to progressive memory deficits in epilepsy, we performed simultaneous in vivo electrophysiology in the hippocampus (HPC) and medial entorhinal cortex (MEC) of control and epileptic mice 3 or 8 weeks after pilocarpine-induced status epilepticus (Pilo-SE). We found that HPC synchronization deficits (including reduced theta power, coherence, and altered interneuron spike timing) emerged within 3 weeks of Pilo-SE, aligning with early-onset, relatively subtle memory deficits. In contrast, abnormal synchronization within the MEC and between HPC and MEC emerged later, by 8 weeks after Pilo-SE, when spatial memory impairment was more severe. Furthermore, a distinct subpopulation of MEC layer 3 excitatory neurons (active at theta troughs) was specifically impaired in epileptic mice. Together, these findings suggest that hippocampal-entorhinal circuit dysfunction accumulates and shifts as cognitive impairment progresses in TLE.